Production of Liquid Hydrocarbons from Plastic Wastes - Dobó, Zsolt; Kecsmár, Gergő; Jakab, Zsófia; Nagy, Gábor; Koós, Tamás (International Journal of Engineering and Management Sciences, 2019)
Thermal pyrolysis of HDPE, LDPE, PP and PS plastic wastes were performed in a batch reactor and the yields of pyrolysis oils and liquid transportation fuels prepared by atmospheric distillation were determined. The gasoline fractions were tested in a traditional spark-ignition engine without any modifications or fuel blending. Fuel consumption and exhaust gas emission (NOx, CO) were measured and compared to a commercial fuel (RON = 95). PS generated 70.5% gasoline range hydrocarbons from the solid waste, followed by PP with 42.1%, LDPE with 40.8% and HDPE with 37.3%. The fuel consumption was reduced by 9.1-9.4% in the case of PS compared to reference measurement. Reduction in fuel consumption was noticeable at HDPE, LDPE and PP as well. PS gasoline decreased by 91-96%, while HDPE, LDPE and PP more likely increased the CO emission of the engine compared to commercial gasoline. The results show that pyrolysis of plastic wastes is a promising method to generate value added liquid transportation fuels and reduce the footprint of waste accumulation in landfills.